(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
There is no doubt that the use of Internet access on a larger scale in today’s society since its inception and evolution has allowed the communication and collaboration of information, crossing barriers of distance and time, which has made it the largest technological resource used today. However, the spread of this tool has not been homogeneous worldwide, causing those who do not have this service to be at a clear disadvantage compared to those who have access to it, therefore, efforts are required to carry out a digital inclusion in areas where there is little or no service. For this, the Mexican government, through public policies of digital development, has promoted projects that fulfill this purpose. One of them is public policy: México Conectado, which helps the state of Tabasco to provide new communication scenarios for Tabasco society.